2023
DOI: 10.2147/ndt.s391897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Childhood Trauma and Adult Separation Anxiety Disorder on Quality of Life in Individuals with Schizophrenia

Abstract: Background: Childhood trauma and anxiety disorders are common in individuals with schizophrenia. This study aimed to investigate the effects of childhood trauma and adult separation anxiety disorder on the quality of life of individuals with schizophrenia. Methods: This cross-sectional study included 111 individuals with schizophrenia and 85 control subjects. The separation anxiety symptom inventory (SASI), adult separation anxiety questionnaire (ASAQ), Positive and Negative Syndrome Scale (PANSS), childhood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A study of 111 patients with schizophrenia and 85 control subjects determined that those with schizophrenia and childhood trauma had increased incidence of adult separation anxiety disorder [ 20 ]. Furthermore, the study found that schizophrenia in the setting of past childhood trauma is associated with increased disease burden [ 20 ]. This association itself may provide a key link between PNES, schizophrenia, and childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 111 patients with schizophrenia and 85 control subjects determined that those with schizophrenia and childhood trauma had increased incidence of adult separation anxiety disorder [ 20 ]. Furthermore, the study found that schizophrenia in the setting of past childhood trauma is associated with increased disease burden [ 20 ]. This association itself may provide a key link between PNES, schizophrenia, and childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic stress experiences cause high levels of anxiety in children, and studies reveal the relationship between childhood traumas and different types of anxiety disorders (Nemeroff, 2016). Separation anxiety seen in adults is among the anxiety types highly correlated with childhood traumas (Karaytuğ et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It also manifests itself with relationship difficulties and inconsistencies caused by fluctuations in self and affect (Faraji, 2021). Childhood traumas and borderline personality traits have a strong association with adulthood separation anxiety (Bassi et al, 2021;Karaytuğ et al, 2023, Namlı et al, 2022. When the child cannot establish a secure bond in his first relationships, he expects to be abandoned in his future relationships, and this expectation reveals the emotional and cognitive processes underlying the formation of anxiety (Astuti et al, 2020).…”
Section: The Mediator Role Of Borderline Personality Features and Sep...mentioning
confidence: 99%